From Isomorphism to Cannibalism: The Evolution of Haroldo de Campos’s Translation Concepts - Cisneros, Odile (TTR, 2012)
This essay charts the evolution of the translation concepts developed by the Brazilian poet Haroldo de Campos from his early concrete phase in the 1950s to what could be termed a postcolonial turn in the 1980s. I argue that the early concept of “transcreation” emerged from the practice of concrete poetry with its isomorphic mirroring of form and content. Stemming from the difficulty of translating concrete poetry and similar isomorphic texts, de Campos suggests a form of translation where a correspondence between the form and content of the original is also sought in the target text. Moving away from primarily formal concerns, in later developments, de Campos lays emphasis on a translation concept that puts forth a critical view of the original through the metaphor of the cannibal, who both reveres and devours the enemy, literally incorporating its energies into his body. This later concept of translation as cannibalism can be read within the larger arena of postcolonial translation. Although De Campos’s concepts were mainly developed independently from the mainstream currents of translation theory, they may be understood in relation to more recent discussions by Lefevere, Bassnett, and Trivedi, among others.